Apkinson — A Mobile Monitoring Solution for Parkinson's Disease - Klumpp, Philipp; Janu, Thomas; Arias Vergara, Tomás; Vasquez Correa, Juan; Rafael Orozco-Arroyave, Juan; Nöth, Elmar (Interspeech 2017, 2017)
In this paper we want to present our work on a smartphone application which aims to provide a mobile monitoring solution for patients suffering from Parkinson’s disease. By unobtrusively analyzing the speech signal during phone calls and with a dedicated speech test, we want to be able to determine the severity and the progression of Parkinson’s disease for a patient much more frequently than it would be possible with regular check-ups. The application consists of four major parts. There is a phone call detection which triggers the whole processing chain. Secondly, there is the phone call recording which has proven to be more challenging than expected. The signal analysis, another crucial component, is still in development for the phone call analysis. Additionally, the application collects several pieces of meta information about the calls to put the results into deeper context. After describing how the speech signal is affected by Parkinson’s disease, we sketch the overall application architecture and explain the four major parts of the current implementation in further detail. We then present the promising results achieved with the first version of a dedicated speech test. In the end, we outline how the project could receive further improvements in the future.<br
Keywords: speech monitoring; pathological speech; Parkinson’s disease